PHYTOCHEMICAL CONSTITUENTS AND ANTIOXIDANT PROPERTIES OF ACETONE EXTRACT OF CLEOME GYNANDRA (L.) GROWING IN THE EASTERN CAPE, SOUTH AFRICA. - Sowunmi, Linda Ifeanyichukwu; Afolayan, Anthony Jide (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Several wild vegetables have been reported for their therapeutic benefits in South Africa. Many of these plants including Cleome gynandra (L.) lack scientific reports on its significance in folkloric medicine. Therefore, this study was undertaken to evaluate quantitatively the compositions of phytochemicals and antioxidant properties of acetone extract of different parts of C. gynandra. Materials and Method: Antioxidant activities were assessed against ferric reducing power, ABTS (2, 2’- azino-bis-3-ethyl benzothiazoline-6-sulfonic acid) diammonium salt, DPPH (1, 1- diphenyl-2-picrylhydrazyl) and NO (nitric oxide) radical scavenging activities. Total phenolics, flavonoids, flavanols, proanthocyanidins, tannins, saponins and alkaloids were also investigated. Results: Amongst the different plant parts, the leaf extract had the highest concentration of total phenolics (126.79 ± 0.55 mg/g), flavonoids (40.58 ± 0.06 mg/g) and flavanols (42.41 ± 0.05 mg/g) while the stem extract had the highest amount of proanthocyanidins (419.01 ± 0.67 mg/g) compared to the leaves (403.29 ± 0.89 mg/g) and fruits (107.18 ± 0.59 mg/g). The reducing power of the extracts was significantly higher than that of the standard drugs used in a concentration dependent manner. The activities of the plant extracts against ABTS, DPPH and NO radicals were dose responsive with IC50 value of 0.2, 0.1 and 0.03 mg/g respectively. Conclusion: C. gynandra possesses high secondary metabolites which accounts for its strong antioxidant ability thus justifying its use as natural occurring antioxidants in folkloric medicine. The study encourages a regular consumption of this wild vegetable in order to avert oxidative stress related diseases.